Aquaporin-4 Polymorphisms Are Associated With Cognitive Performance in Parkinson’s Disease - Fang, Yi; Dai, Shaobing; Jin, Chongyao; Si, Xiaoli; Gu, Luyan; Song, Zhe; Gao, Ting; Chen, Ying; Yan, Yaping; Yin, Xinzhen; Pu, Jiali; Zhang, Baorong (Frontiers in Aging Neuroscience, 2022)
Objective Aquaporin-4 (AQP4) facilitates a sleep-enhanced interstitial brain waste clearance system. This study was conducted to determine the clinical implication of AQP4 polymorphisms in Parkinson’s disease (PD). Methods 382 patients with PD and 180 healthy controls with a mean follow-up time of 66.1 months from the Parkinson’s Progression Marker Initiative study were analyzed. We examined whether AQP4 SNPs were associated with an altered rate of motor or cognitive decline using linear mixed model and Cox regression. We then investigated whether AQP4 SNPs were associated with Aβ burden as measured by 18F Florbetapir standard uptake values. Furthermore, we examined if AQP4 SNPs moderated the association between REM sleep behavior disorder (RBD) and CSF biomarkers. Results In patients with PD, AQP4 rs162009 (AA/AG vs. GG) was associated with slower dementia conversion, better performance in letter-number sequencing and symbol digit modalities, lower Aβ deposition in the putamen, anterior cingulum, and frontotemporal areas. In the subgroup of high RBD screening questionnaire score, rs162009 AA/AG had a higher CSF Aβ42 level. rs162009 AA/AG also had better performance in semantic fluency in healthy controls. Besides, rs68006382 (GG/GA vs. AA) was associated with faster progression to mild cognitive impairment, worse performance in letter-number sequencing, semantic fluency, and symbol digit modalities in patients with PD. Interpretation Genetic variations of AQP4 and subsequent alterations of glymphatic efficacy might contribute to an altered rate of cognitive decline in PD. AQP4 rs162009 is likely a novel genetic prognostic marker of glymphatic function and cognitive decline in PD.